PENGARUH KEMASAN SERTA KONDISI DAN LAMA PENYIMPANAN TERHADAP PERTUMBUHAN Staphylococcus aureus PADA DAGING SEI BABI - Erda Eni Rame Hau (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
In addition to be sold freshly for consumption after being processed, se’í babi which is a popular meat product of Kupang City has also been given a vacuum packing processing with the aim to extend the shelf life of meat. This research aims to determine the effect of the packaging and storage conditions of seí babi from four meat shops in the Kupang to the growth and number of pathogenic microorganisms Staphylococcus aureus up to the some certain time. S. aureus is one of foodborne disease bacteria that can contaminate meats. Bacterial contamination can come from the environment or bacterial infections in farm. Total of 16 se’i babi samples were used in this research, 2 samples from each meat shops. Two different packaging samples from all shops were then stored in two different conditions (room temperature and refrigerator). Samples were then being proceeded for S. aureus microbial evaluation every day since day-0 to day-5. Samples were cultured on Baird Parker medium and Mannitol Salt Agar and followed by bacteria identification by Gram stain, catalase test, oxidase test, and coagulase test. The number of S. aureus colonies was calculated and the result was compared to the limit of microbial contamination based on Standar Nasional Indonesian (SNI). The number of S. aureus from day 1 until day 5 of all samples were > 1 × 102 CFU/g, more than SNI (7388:2009). The results showed differences in the total number of bacteria between meats on refrigerator temperature storage, which is in general is lower compared to meat in room temperature storage. The same trend also occurs in vacuum packed meats, they had lower number of S. aureus compared to samples without vacuum packed.